Assessing Worry in Children: Psychometric Evaluation of the Indonesian Version of the Penn State Worry Questionnaire for Children (PSWQ-C) - Annastasia Ediati; Agustini Utari (Universitas Ahmad Dahlan, 2019)
The Penn State Worry Questionnaire for Children (PSWQ-C) is a well-known 14-items self-report measure of worry in children and adolescents. Previous studies reported favorable psychometric properties in clinical and non-clinical samples, but recommendations given to use the full version or the shortened version of PSWQ-C are inconclusive. As a standardized measure of worry was not available in Indonesia prior to the study, the present study aims to evaluate the Indonesian version of PSWQ-C as a measure of worry on children and to assess worry in a large non-clinical sample of Indonesian children. We conducted forward-backward translation and applied the Indonesian translation of PSWQ-C on 653 children (3rd to 5thgrades) from four state elementary schools in Semarang city. Furthermore, we also conducted comparison analysis across gender and grades. Principal component analysis resulted in two-factor structure of 14 items as well as a one-factor structure comprised 11 items. The reversed scoring items had poor psychometric qualities. The Indonesian version of 11-items PSWQ-C has satisfactory internal consistency (Î± = 0.808). Young girls significantly scored higher than boys, but no significant differences were found across grades. The Indonesian version of the 11-item PSWQ-C demonstrated favorable psychometric properties to be applied in the future studies. Intervention to prevent or reduce anxiety and depression in young children should consider gender and grades differences.Â